Agriculture development in ensuring economic security in uzbekistan: theory, analysis and prospects - Bekmirzayev, Mirzohid (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
As a result of the last five-year reforms the necessary political-legal, socio-economic and scientific-educational foundations for the establishment of New Uzbekistan were created at the new stage of development of our country,. Development strategy of New Uzbekistan consisting of seven priority directions for 2022-2026 was approved. As in all sectors, a number of reforms have been carried out in agriculture to ensure the economic security of the state, sustainable development of the agricultural sector, food security of the population, creating a favorable agribusiness environment and added value chain, reducing state participation in management and increasing investment attractiveness, rational use of natural, labor and material and technical resources in the network, optimal placement of crops, processing of agricultural products, improving the quality of seed production and breeding, increasing the capacity of personnel in the network, acceleration of such important tasks as scientific-research works and improvement of information supply are being solved step by step.